Serum ferritin as indicator of iron responsive anaemia in patients with rheumatoid arthritis. Issue 7 (July 1986) - Hansen, T M; Hansen, N E
Abstract : In order to test the hypothesis that serum ferritin below 60 micrograms/l is a good indicator of iron deficiency in patients with rheumatoid arthritis peroral iron was given to 67 patients with active rheumatoid arthritis over a three month period. A rise in haemoglobin concentration was taken as evidence of iron responsive anaemia. In anaemic patients serum ferritin below 60 micrograms/l was a good indicator of iron responsive anaemia, with a predictive value of 83%. Although high plasma transferrin and low mean cell volume showed similar predictive values, more patients with iron deficiency anaemia could be diagnosed by serum ferritin measurements than by other conventional blood tests. In contrast, the predictive value of serum ferritin above 60 micrograms/l was low (50%). The test was of no predictive value in non-anaemic patients. In patients with anaemia and active rheumatoid arthritis serum ferritin is the best blood test currently available for the prediction of iron responsive anaemia.